Alternating Optimization Method for Isogeometric Topology Optimization with Stress Constraints (Journal of Computational Mathematics, 2023)
Topology optimization (TO) has developed rapidly recently. However, topology optimization with stress constraints still faces many challenges due to its highly non-linearproperties which will cause inefficient computation, iterative oscillation, and convergenceguarantee problems. At the same time, isogeometric analysis (IGA) is accepted by moreand more researchers, and it has become one important tool in the field of topology optimization because of its high fidelity. In this paper, we focus on topology optimization withstress constraints based on isogeometric analysis to improve computation efficiency andstability. A new hybrid solver combining the alternating direction method of multipliersand the method of moving asymptotes (ADMM-MMA) is proposed to solve this problem.We first generate an initial feasible point by alternating direction method of multipliers(ADMM) in virtue of the rapid initial descent property. After that, we adopt the methodof moving asymptotes (MMA) to get the final results. Several benchmark examples areused to verify the proposed method, and the results show its feasibility and effectiveness.
Keywords: Isogeometric topology optimization; Stress constraints; The ADMM-MMA solver.